Acceptance and usage, social influences, instructor’s presence and performance among learners in an ODL institution - Raemah Abdullah Hashim,; Loo , Sin Chun; Yanty Roslinda Harun,; Zahir Osman,; Zulaika Zakariah,; Nor Fairuz Syazana Nor Fauzi, (ASEAN Journal of Open and Distance Learning, 2019)
Open Distance Learning (ODL) has been implemented in Malaysia for several decades to widen access to education while enriching the quality of learner's experience. Building from previous literature, this article aims to examine the relationship between independent variables of learner acceptance and usage of e-learning and instructor presence and learner performance, as the dependent variable, while social influences act as the mediation variable among learners in a distance learning (ODL) environment. Working adults enrolled for business programmes in one of the ODL institutions in Malaysia were surveyed. A total of 148 participants completed a survey questionnaire measuring their responses on the said variables. The study found that there was a positive relationship between the two independent constructs and learner performance. Social influences fully mediated between the independent and dependent variables. This indicates that peer influence is important during the learning process and the delivery of the teaching will enhance the learner’s competencies and knowledge. These findings indicate that these variables can be included in ODL learning environment. However, other constructs should also be explored. Suggestions and recommendations on the strength and influence of these variables to working adults are discussed and their applicability in other cultures and ODL institutions are elaborated upon. (Abstract by authors)